Upon Synthesis of Poly(N-isopropylacrylamide-co-2-dimethyl-aminoethyl methacrylate-co-itaconic acid) Copolymers as Matrix Ensuring Intramolecular Strategies for Further Coupling Applications - Chiriac, Aurica P.; Nita, Loredana E.; Neamtu, Iordana; Balan, Vera; Diaconu, Alina (Journal of Research Updates in Polymer Science, 2014)
The study presents a set of copolymers synthesis based on N-isopropylacrylamide, 2-dimethylaminoethyl methacrylate and itaconic acid comonomers found in different gravimetric ratio, acquired through polymerization in water in the presence of ammonium persulfate as radical initiator. The purpose was to prepare polymeric structure with dual sensitivity to temperature and pH respectively, and able as well to ensure intramolecular strategies for coupling applications of inorganic or bioactive compounds. The polymers composition was confirmed by FTIR and 1H-NMR spectra. The thermal stability of the polymeric compounds was evaluated, and SEM investigations of the polymer morphology are also presented. The polymers dispersions were characterized from the viewpoint of their hydrodynamic radius, zeta potential and conductivity.